Pattern Of Municipal Expenditure And Budgeting With Reference To Nepalese Municipalities - Narayan Prasad Paudel, (Journal of Contemporary Review, 2025)
This study examines the revenue and expenditure patterns of Nepalese municipalities, focusing on the role of local revenue in financing municipal activities. Municipal expenditures are categorized into regular, capital, and social development activities, with grants-in-aid, surplus revenue, and cost-sharing as key sources for development financing. Regression analysis reveals that 77.6% of total expenditure is explained by local revenue, while 19.1% is contributed by local development charges, indicating the significant role of internally generated funds in municipal spending. Correlation analysis shows a strong positive relationship between total revenue and expenditure, confirming that expenditure closely follows revenue trends. The study further employs the Coefficient of Vertical Imbalance, which highlights an increasing reliance on central government grants over the study period, despite growth in local revenue. Findings underscore the importance of improving local financial management, enhancing transparency, and addressing region-specific challenges in the allocation and utilization of development funds. Strengthening local revenue mobilization and optimizing the use of development charges are essential for sustainable municipal development and reduced dependence on central transfers